Dalit theology and Christian anarchism - Hebden, Keith (Farnham, UK ; Burlington, VT : Ashgate, 2011)
A second generation of emerging Dalit theology texts is re-shaping the way we think of Indian theology and liberation theology. This book is a vital part of that conversation. Taking post-colonial criticism to its logical end of criticism of statism, Hebden looks at the way the emergence of India as a nation state shapes political and religious ideas. Keith draws on historical trends, Christian anarchist voices and the religious experiences of indigenous Indians.
Subversion and resistance in postcolonial discourse -- Cosmic courtship and the violence of the gods -- Self preservation society -- Missiological controversies on church and state -- Fathers of the nation : the Gandhi and Ambedkar controversy -- Resistance from the margins -- Dalit theology and the powers that be -- Jesus the foreigner.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Dalits -- India -- Religion; Liberation theology -- India; Christian anarchism; RELIGION / Christian Theology / Liberation; Electronic books